Africas Dependency Syndrome : Can Africa Still Turn Things around for the Better? - Mhango, Nkwazi Nkuzi (Book collections on Project MUSE., 2017)
There are milliards of off beam assumptions that Africa will always remain immobile in development of whatever type. This pseudo take has mainly been propounded by Western thinkers in order to dubiously make Africans internalise and reinforce this flimsy and flimflam dependency. Africa needs to embark on paradigm shift; and tweak and turn things around. Africa has what it take to do so quickly, especially now that new economic powers such as China and India are evolving as counterweight to the West. Shall Africa use these new economic forces to its advantage based on fair and win-win cooperation? To do so, Africa must make sure that it does not slink back into business as usual vis-a-vis beggarliness, dependence, frailty, gullibility, made-up backwardness, monkey business, and pipedreams, not to mention the nasty and narcissistic behaviours of its venal and navel-gazing rulers. Verily, Africa needs, inter alia, to use its God-given gifts, namely, immense resources, young population, abundance of vast and unexploited amounts of land. Equally, Africa must, without equivocation, invest copiously and earnestly in its people, the youth in the main. Most of all, Africa needs to shy away from all colonial carryovers and encumbrances. This volume shows many ways through and by which Africa can inverse the current imbroglio-cum-no-go it faces for the better; and thereby actualise the dream of being truly independent and prosperous.